Facile single-step bioconjugation of the antifungal agent caspofungin onto material surfaces via an epoxide plasma polymer interlayer. Issue 44 (24th May 2017) - Michl, Thomas D.; Giles, Carla; Cross, Alasdair T.; Griesser, Hans J.; Coad, Bryan R.
Abstract : We report a facile, one-step, aqueous surface bioconjugation approach for producing an antifungal surface coating that prevents the formation of fungal biofilms. Abstract : We report a facile, one-step, aqueous surface bioconjugation approach for producing an antifungal surface coating that prevents the formation of fungal biofilms. By direct reaction between surface epoxide groups and amine groups on caspofungin, it avoids the use of secondary chemicals. The coating withstands washing with detergent and reduces the growth of the fungal pathogens Candida albicans by log 6 and Candida glabrata by log 3. Importantly, we show that surface adsorption of albumin does not inhibit the activity of this antifungal coating.